Rodinný dům na Nových Dvorech - Truhlář, Jan (Vysoké učení technické v Brně. Fakulta stavební)
Bakalářská práce se zabývá vypracováním projektové dokumentace pro provádění stavby pro rodinný dům na Nových Dvorech. Rodinný dům je navržen částečně podsklepený s jedním nadzemním podlažím a obytným podkrovím. Jedná se o samostatně stojící objekt tvaru L. Zastřešen částečně plochou a částečně sedlovou střechou. Zdivo nad terénem je z tvárnic Porotherm, zdivo pod terénem je navrženo ze ztraceného bednění objekt je zateplen systémem ETICS . Založení domu je navrženo na betonových základových pasech. Stropy jsou navrženy jako železobetonové desky. Schodiště bude železobetonové. Krov je navržen jako hambálková soustava. Střešní krytina bude skládaná betonová taška. Plochá střecha je navržena vegetační.

This bachelor thesis deals with the elaboration of the project documentation for the construction of the new family house in Nové Dvory. This family house is designed with partial basement with one floor and an attic flat. I tis a free-standing object in the L-form. The house is roofed partly with a flat roof and partly with a gable roof. The masonry above the terrain consists of the Porotherm blocks. The masonry under the terrain consists of the permanent formwork. The object is insulated with the ETICS thermal insulation system. The foundation construction is designed on the concrete strip footing. The ceilings are constructed as reinforced concrete slabs. The stairs will be also of the einforced concrete. The roof truss is designed as collar beam system. The roof covering will be the prefabricated concrete tile. The flat roof is projected as green roof.
Detached house in Nové Dvory
Keywords: Bakalářská práce; rodinný dům; plochá střecha; sedlová střecha; kontaktní zateplovací systém; Bachelor thesis; detached house; flat roof; gable roof; contact thermal insulation system